2008
DOI: 10.1001/archpsyc.65.11.1269
|View full text |Cite
|
Sign up to set email alerts
|

Familial Predisposition for Psychiatric Disorder

Abstract: Predisposition to both psychiatric disorders in general and psychotic disorders specifically contributes equally to the risk of later treatment because of schizophrenia and cannabis-induced psychoses. Cannabis-induced psychosis could be an early sign of schizophrenia rather than a distinct clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The vast majority of studies linking candidate genes and cannabis use to psychiatric symptoms are related to schizophrenia or psychotic illnesses. Several studies support a relationship between family psychiatric history and increased likelihood of psychotic symptoms associated with cannabis use [213215]. Psychosis liability has also been shown to potentiate the psychotomimetic effects of acute cannabis use[15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies linking candidate genes and cannabis use to psychiatric symptoms are related to schizophrenia or psychotic illnesses. Several studies support a relationship between family psychiatric history and increased likelihood of psychotic symptoms associated with cannabis use [213215]. Psychosis liability has also been shown to potentiate the psychotomimetic effects of acute cannabis use[15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…The model put forth in this paper would presume that the culpable environmental factor is related to lower light levels in northerly climates, although the effect of the stress of immigrating to a different culture cannot easily be discounted, as discussed by Coid et al (2008). In addition, rates of usage of illicit drugs may be higher amongst Afro-Caribbeans immigrants, particularly of concern if the drug of choice is cannabis (McGuire et al, 1995; Moore et al, 2007; Arendt et al, 2008; Di Forti et al, 2009; McGrath et al, 2010b). The rate of cannabis use in the Afro-Caribbean immigrant population may be somewhat higher vs. long term residents of the U.K. (Harvey et al, 1990) but may not be higher than rates in their home countries which have been reported to be already quite high (reviewed by Sugarman and Craufurd, 1994; Maharajh and Konings, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that both environmental factors and genetic predisposition play a role in this causal association. Consistent with this notion, among patients with schizophrenia, hypersensitivity to the psychotomimetic effects of cannabis is associated with early cannabis exposure and a family history of psychosis (Arendt et al, 2008; Goldberger et al, 2010); moreover, a recent study of a large sample of students found that sensitivity to the psychotomimetic effects of cannabis appears to be an intrinsic feature present since the first exposure to cannabis (Krebs et al, 2014). …”
Section: Long-term Effects Of Cannabis Use During Adolescence In Humansmentioning
confidence: 92%